- PEMAHAMAN HUKUM KEKAYAAN INTELEKTUAL BAGI CIVITAS AKADEMIKA DI PERGURUAN TINGGI: - - sudjana sudjana (Fakultas Seni Rupa dan Desain ITB, 2021)
This study is to determine the efforts to improve the understanding of Intellectual Property Law of students and lecturersin Higher Education. The method used is descriptive qualitative, namely identifying the understanding of IntellectualProperty Law of the academic community in Higher Education, which is then analyzed qualitatively. The results of thestudy show that providing students with understanding of Intellectual Property Law in Higher Education can be donethrough a structured teaching and learning process by developing a curriculum according to the substance based on thetype of Intellectual Property, by paying attention to the learning formats, namely attitudes, knowledge and skills, and byevaluating the three aspects. The effort that can be done by faculties that do not have the curriculum is embedding theIntellectual Property Law as a compulsory or elective course. To increase the understanding of Intellectual Property Lawamong lecturers can be done through their active role in scientific activities.